2001
DOI: 10.1063/1.1350412
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Monte Carlo study of structural relaxation in vitreous selenium

Abstract: Vitreous selenium is used extensively for light detection. Its photoconducting properties are altered by structural relaxation near room temperature. X-ray diffraction, densiometry, and calorimetry are used to determine the change of the glass state during relaxation. Annealing for 24 h at 300 K increases the density by 0.14% and lowers the enthalpy by 105 J/mol. The structure factor of cast samples was measured before and after annealing, and reverse Monte Carlo models of the structure of selenium glass were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Brüning et al 24 investigated the change of enthalpy upon aging a glass for 14 h at Tϭ300 K and find an increase in density by 0.14% and a lowering of enthalpy by 1 meV/ atom. We would expect to find similar values upon changing the quench rate from the experimental value of 10 K/min to something like 1 K/h.…”
Section: Discussionmentioning
confidence: 99%
“…Brüning et al 24 investigated the change of enthalpy upon aging a glass for 14 h at Tϭ300 K and find an increase in density by 0.14% and a lowering of enthalpy by 1 meV/ atom. We would expect to find similar values upon changing the quench rate from the experimental value of 10 K/min to something like 1 K/h.…”
Section: Discussionmentioning
confidence: 99%
“…the dihedral angle φ and the inter-chain distance R [18,19]. A single chain may be longer than 10 5 in the atom number [12,18].…”
Section: (A)mentioning
confidence: 99%
“…4, 5, 7, and 8 were calculated by a curve fitting technique by using Eqs. (12), (13), and (15) for the set of AGS parameters corresponding to volume relaxation ( Table 2).…”
Section: Isothermal Volume Relaxationmentioning
confidence: 99%
“…They found that the times to reach equilibrium appear to be the same in the vicinity of the glass transition temperature, but seem to diverge at lower temperatures with enthalpy coming to equilibrium before volume and creep. Enthalpy relaxation of vitreous Se, the contributing microscopic processes and their entropic relation has been discussed by Bruning et al [12].…”
Section: Introductionmentioning
confidence: 98%